Rilpivirine Pharmacokinetics Without and With Darunavir/Ritonavir Once Daily in Adolescents and Young Adults. Issue 9 (September 2016) - Foca, Marc; Yogev, Ram; Wiznia, Andrew; Hazra, Rohan; Jean-Philippe, Patrick; Graham, Bobbie; Britto, Paula; Carey, Vincent J.; King, Jennifer; Acosta, Edward P.; Cressey, Tim R.
Abstract : Background: Rilpivirine (RPV), a recently developed, once daily human immunodeficiency virus non-nucleoside reverse transcriptase inhibitor, is not currently approved for pediatric patients, but is sometimes prescribed for adolescents with multiple treatment failures, for regimen simplification or to minimize toxicity. Darunavir/ritonavir (DRV/r) administered once daily is also increasingly used in adolescents and may alter RPV pharmacokinetics (PK). We evaluated the PK interactions between RPV and DRV/r once daily in adolescents and young adults. Methods: Human immunodeficiency virus–infected subjects 12 to <24 years old receiving a stable background therapy including RPV 25 mg once daily without or combined with DRV/r 800/100 mg once daily were enrolled. Intensive 24-hour blood sampling was performed, and PK indices were determined using noncompartmental analysis. Protocol-defined target drug exposure ranges based on adult data were used to assess the adequacy of each regimen. Results: Fifteen subjects receiving RPV without and 14 subjects with DRV/r were enrolled. When dosed without DRV/r, the RPV geometric mean (90% confidence interval) for RPV AUC0-24, C max and C 24 h were 2.38 μg h/mL (1.92–2.94), 0.14 μg/mL (0.12–0.18) and 0.07 μg/mL (0.03–0.10), respectively, similar to adult values. RPV concentrations were significantly increased with concomitant DRV/r use: RPV AUC24, C max and C 24 h were 6.74 μg h/mL (4.89–9.28), 0.39 μg/mL (0.27–0.57) and 0.23 μg/mL (0.17–0.32), respectively, well above the target ranges based on adult data. DRV/r PK was not affected by coadministration of RPV. Conclusions: RPV PK in this adolescent population was similar to adults when dosed without DRV/r. DRV/r coadministration increased RPV exposure 2- to 3-fold, indicating that drug-related side effects should be closely monitored.